Pengukuran Dan Evaluasi Risiko Ergonomi Pada Pekerja Angkat Angkut Di Ekspedisi Dengan Metode Rapid Entire Body Assesment (REBA) - Novira Alifia Putri; Afrilia Dwi Maharani; Putri Dwi Rohmahwati; Safira Afni Syahbilla; Denny Oktavina Radianto (Jurnal Medika Nusantara, 2023)
Human labor is still widely used in many sectors or fields in Indonesia, especially work in the field of lifting and carrying. In the lifting and carrying work system, what often happens is complaints of musculoskeletal pain which is the most common complaint experienced by workers worldwide (Agistha Novta Auliya et al., 2021). This research was conducted at PT. Jaya Mas with the object of research, namely 2 lift workers on the expedition. The method used by researchers in this study is a quantitative method by collecting interview data and a survey of complaints of skeletal muscle disorders referring to SNI 9011-2021. And using REBA to identify the risks of MSDs in workers. The results of the GOTRAK questionnaire recapitulation showed high risk category values for 5 body parts, namely the lower back, right hip, left hip, right leg, and left leg. Whereas the REBA method produces a value of 5 which belongs to the medium hazard risk category. Recommendations that can be given to lift workers at PT. Jaya Mas is moving heavy loads using a machine or troller, using a table that can go up and down, and reducing large workloads using the help of gravity such as making manual slides with wooden plywood.